433. Impact of Malaria Prophylaxis on Risk of Travelers' Diarrhea Among International Travelers. (26th November 2018) - Lago, Kathryn; Telu, Kalyani; Tribble, David R; Ganesan, Anuradha; Kunz, Anjali; Geist, Charla; Fraser, Jamie; Mitra, Indrani; Lalani, Tahaniyat; Yun, Heather
Abstract: Background: International travelers are often at risk for travelers' diarrhea (TD) and malaria. Doxycycline has activity against pathogens causing TD but hasn't been used as TD prophylaxis since the 1980s when resistance emerged. We evaluated the incidence of and risk factors for TD, and whether the choice of malaria prophylaxis was associated with risk of TD. Methods: TravMil is a prospective observational study enrolling subjects presenting to six military travel clinics. We analyzed pre- and post- travel surveys from travelers to regions outside of the continental United States, Western or Northern Europe, Canada or New Zealand between July 2010 and August 2018. TD was defined as ≥3 loose stools in a 24-hour period or two liquid or loose stools in a 24-hour period and ≥1 of the following: nausea, vomiting, abdominal pain, fever, or bloody stool. Characteristics of trip and traveler, and use of malaria prophylaxis (doxycycline, other, and none) were analyzed to determine risk factors for TD. A Poisson regression model with robust error variance was used to estimate relative risk of TD. Results: A total of 3, 227 travelers enrolled: 62.1% male, median age of 39 (IQR 27, 59), median travel duration 19 days (IQR 12, 49). 17.4% developed TD. 32% traveled to Africa, 40% to Asia, and 27% to the Caribbean, Mexico, Central, or South America. Military travel (46%) and vacation (40%) were most common reasons for travel. 20% took doxycycline for malaria prophylaxis, 50% other prophylaxis (89% atovaquone-proguanil), and 30% took none. Compared with those on no or other prophylaxis, doxycycline was associated with decreased risk for TD [RR 0.62 (0.47–0.82), P < 0.01], as was military travel [RR 0.57 (0.47–0.70), P < 0.01]. Increased risk of TD was associated with female gender [RR 1.28 (1.09–1.50), P < 0.01], staying in a hotel [RR 1.30 (1.10–1.53), P < 0.01], travel to tropical South America [RR 1.34 (1.09–1.64), P < 0.01], and duration of travel [RR 1.00 (1.00–1.01), P < 0.01]. Conclusion: Compared with taking other or no prophylaxis, use of doxycycline for malaria prophylaxis is associated with lower TD risk, suggesting potential changes in resistance patterns, anti-inflammatory effects, or association with other unmeasured risk factors. Doxycycline may impact TD risk independently of other risk factors. Disclosures: All authors: No reported disclosures.